Where the forest meets the sea - Baker, Jeannie (New York : Greenwillow Books, 1987)
On a camping trip in an Australian rain forest with his father, a young boy thinks about the history of the plant and animal life around him and wonders about its future.
Book Links (A.L.A.)
School Library Journal starred
Wilson's Children
2.5
K-3.
K-3
Keywords: Rain forests -- Juvenile fiction; Rain forests -- Fiction; Rain forests -- Fiction; Australia -- Juvenile fiction; Australia -- Fiction; Australia -- Fiction